Advice for chief nurses on integrating LGBTQ+ inclusive practices into the healthcare system through centred qualitative exploration - Nguyen Cheirard; Labrag Gretha (Safety and Health for Medical Workers, 2024)
Objective: This research aims to uncover effective strategies for fostering an equitable environment for LGBTQ+ individuals as well as potential barriers to achieving this and classifies these strategies based using the Expert Recommendations for Implementing Change (ERIC) framework.Methods: We conducted a qualitative exploration using in-depth interviews with chief nurses at a selected sample of healthcare organizations throughout Thailand. Thematic analysis was performed to identify recurring themes and classify strategies according to the ERIC framework.Findings: The study highlighted five factors that influenced the application of LGBTQ+-inclusive practices: corporate training programs, clarity in organization policy and directives, support from management,  tackling culture in the organization, and (5) staff participation in continuous education. Training programs, as well as clear policy implementation, had the largest hits amongst these. The accessibility of information, combined with cultural and behavioral changes, could be contributing to the recent increase in segregation, the authors argue, and cultural resistance continues to be a significant barrier, suggesting that targeted efforts are needed to address underlying biases. Moreover, through community engagement and a digital learning tocreate breaking routes for inclusivity emerged as one of the innovative ways.Novelty: The study uniquely integrates qualitative exploration and the ERIC-framework to yield actionable recommendations for chief nurses. It draws attention to other seemingly overlooked barriers including cultural resistance and suggests creative solutions customized to the socio-cultural setting of Thailand, not mentioned in other literature.Research Implications: The insights provide practical advice for healthcare executives who want to foster inclusive settings for LGBTQ+ patients. The study highlights many of the necessary conditions tailored strategy, staff training, and policy implementation for achieving equity in health-care delivery.” These themes will provide guidance to chief nurses in Thailand as well as other areas where socio-cultural behaviours can govern clinical activity, and they provide a pathway to wider adoption of inclusive behaviours in global healthcare systems.